Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To determine which ordered pair makes both inequalities true, let's analyze each pair step-by-step.
Given inequalities:
[tex]\[ y > -2x + 3 \][/tex]
[tex]\[ y \leq x - 2 \][/tex]
We need to check these conditions for the following ordered pairs: \((0,0)\), \((0,-1)\), \((1,1)\), and \((3,0)\).
1. For the ordered pair \((0,0)\):
- Check the first inequality: \(y > -2x + 3\)
- Substitute \(x = 0\) and \(y = 0\):
[tex]\[0 > -2(0) + 3 \Rightarrow 0 > 3\][/tex]
- This is false.
- Since the first inequality is not satisfied, we do not need to check the second one.
2. For the ordered pair \((0,-1)\):
- Check the first inequality: \(y > -2x + 3\)
- Substitute \(x = 0\) and \(y = -1\):
[tex]\[-1 > -2(0) + 3 \Rightarrow -1 > 3\][/tex]
- This is false.
- Since the first inequality is not satisfied, we do not need to check the second one.
3. For the ordered pair \((1,1)\):
- Check the first inequality: \(y > -2x + 3\)
- Substitute \(x = 1\) and \(y = 1\):
[tex]\[1 > -2(1) + 3 \Rightarrow 1 > 1\][/tex]
- This is false.
- Since the first inequality is not satisfied, we do not need to check the second one.
4. For the ordered pair \((3,0)\):
- Check the first inequality: \(y > -2x + 3\)
- Substitute \(x = 3\) and \(y = 0\):
[tex]\[0 > -2(3) + 3 \Rightarrow 0 > -6 + 3 \Rightarrow 0 > -3\][/tex]
- This is true.
- Check the second inequality: \(y \leq x - 2\)
- Substitute \(x = 3\) and \(y = 0\):
[tex]\[0 \leq 3 - 2 \Rightarrow 0 \leq 1\][/tex]
- This is true.
Since the ordered pair \((3,0)\) satisfies both inequalities, the answer is:
[tex]\[ \boxed{(3,0)} \][/tex]
Given inequalities:
[tex]\[ y > -2x + 3 \][/tex]
[tex]\[ y \leq x - 2 \][/tex]
We need to check these conditions for the following ordered pairs: \((0,0)\), \((0,-1)\), \((1,1)\), and \((3,0)\).
1. For the ordered pair \((0,0)\):
- Check the first inequality: \(y > -2x + 3\)
- Substitute \(x = 0\) and \(y = 0\):
[tex]\[0 > -2(0) + 3 \Rightarrow 0 > 3\][/tex]
- This is false.
- Since the first inequality is not satisfied, we do not need to check the second one.
2. For the ordered pair \((0,-1)\):
- Check the first inequality: \(y > -2x + 3\)
- Substitute \(x = 0\) and \(y = -1\):
[tex]\[-1 > -2(0) + 3 \Rightarrow -1 > 3\][/tex]
- This is false.
- Since the first inequality is not satisfied, we do not need to check the second one.
3. For the ordered pair \((1,1)\):
- Check the first inequality: \(y > -2x + 3\)
- Substitute \(x = 1\) and \(y = 1\):
[tex]\[1 > -2(1) + 3 \Rightarrow 1 > 1\][/tex]
- This is false.
- Since the first inequality is not satisfied, we do not need to check the second one.
4. For the ordered pair \((3,0)\):
- Check the first inequality: \(y > -2x + 3\)
- Substitute \(x = 3\) and \(y = 0\):
[tex]\[0 > -2(3) + 3 \Rightarrow 0 > -6 + 3 \Rightarrow 0 > -3\][/tex]
- This is true.
- Check the second inequality: \(y \leq x - 2\)
- Substitute \(x = 3\) and \(y = 0\):
[tex]\[0 \leq 3 - 2 \Rightarrow 0 \leq 1\][/tex]
- This is true.
Since the ordered pair \((3,0)\) satisfies both inequalities, the answer is:
[tex]\[ \boxed{(3,0)} \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.